2012
DOI: 10.4269/ajtmh.2012.11-0817
|View full text |Cite
|
Sign up to set email alerts
|

Potential P-Glycoprotein-Mediated Drug-Drug Interactions of Antimalarial Agents in Caco-2 cells

Abstract: Abstract. Antimalarials are widely used in African and Southeast Asian countries, where they are combined with other drugs for the treatment of concurrent ailments. The potential for P-glycoprotein (P-gp)-mediated drug-drug interactions (DDIs) between antimalarials and P-gp substrates was examined using a Caco-2 cell-based model. Selected antimalarials were initially screened for their interaction with P-gp based on the inhibition of rhodamine-123 (Rho-123) transport in Caco-2 cells. Verapamil (100 μM) and qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The results showed the suitability of these two cell monolayer models to investigate P-gp function in vitro and exhibited similar basic transport characteristics of digoxin compared to data from several reports [37,38] . Although there are well-documented reports on the use of PMA to induce the PKC signaling pathway and its potent effect on drug resistance in cancer cells, this is the first report to investigate the effect of PKC activation by PMA on the P-gp-mediated efflux of digoxin using the Caco-2 and MDCKII-MDR1 cell transport models.…”
Section: Discussionsupporting
confidence: 58%
“…The results showed the suitability of these two cell monolayer models to investigate P-gp function in vitro and exhibited similar basic transport characteristics of digoxin compared to data from several reports [37,38] . Although there are well-documented reports on the use of PMA to induce the PKC signaling pathway and its potent effect on drug resistance in cancer cells, this is the first report to investigate the effect of PKC activation by PMA on the P-gp-mediated efflux of digoxin using the Caco-2 and MDCKII-MDR1 cell transport models.…”
Section: Discussionsupporting
confidence: 58%
“…42,43 Interestingly, in patients receiving NVP-based ART, the defective variant ABCB1 3435 TT genotype was significantly associated with high lumefantrine plasma concentration. Similarly, a previous study reported nonsignificant increase of lumefantrine clearance (13%) in carriers of homozygous wild type for CYP3A5*3.…”
Section: Discussionmentioning
confidence: 97%
“…The P-gp, membrane transporter protein, has a crucial role in the modulation of absorption, distribution, metabolism and excretion of drugs. P-gp is also known to function as a barrier protein to extrude toxins and xenobiotics from cells (4,5). P-gp is able to efflux various anticancer drugs out of the cells in order to decrease the intracellular accumulation of cytostatic drugs, including doxorubicin and paclitaxel (5).…”
Section: Introductionmentioning
confidence: 99%